Phonetic Encoding of Coda Voicing Contrast under Different Focus Conditions in L1 vs. L2 English - Choi, Jiyoun; Kim, Sahayng; Cho, Taehong (Frontiers in Psychology, 2016)
This study investigated how coda voicing contrast in English would be phonetically encoded in the temporal vs. spectral dimension of the preceding vowel (in vowel duration vs. F1/F2) by Korean L2 speakers of English, and how their L2 phonetic encoding pattern would be compared to that of native English speakers. Crucially, these questions were explored by taking into account the phonetics-prosody interface, testing effects of prominence by comparing target segments in three focus conditions (phonological focus, lexical focus, and no focus) that stem from information structure. Results showed that Korean speakers utilized the temporal dimension (vowel duration) to encode coda voicing contrast, but failed to use the spectral dimension (F1/F2), reflecting their native language experience—i.e., with a more sparsely populated vowel space in Korean, they are less sensitive to small changes in the spectral dimension, and hence fine-grained spectral cues in English are not readily accessible. Results also showed that along the temporal dimension, both the L1 and L2 speakers hyperarticulated coda voicing contrast under prominence (when phonologically or lexically focused), but hypoarticulated it in the non-prominent condition. This indicates that low-level phonetic realization and high-order information structure interact in a communicatively efficient way, regardless of the speakers’ native language background. The Korean speakers, however, used the temporal phonetic space differently from the way the native speakers did, especially showing less reduction in the no focus condition. This was also attributable to their native language experience—i.e., the Korean speakers’ use of temporal dimension is constrained in a way that is not detrimental to the preservation of coda voicing contrast, given that they fail to add additional cues along the spectral dimension. The results imply that the L2 phonetic system can be more fully illuminated through an investigation of the phonetics-prosody interface that is further modulated by higher-order linguistic structure such as information structure as well as by the L2 speakers’ native language experience.